The issue of PD estimation - a practical approach - Siarka, Paweł (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2011)
The issue of estimating the probability of default constitutes one of the foundations of risk systems applied in modern banking. The Basel Committee pays a lot of attention to ways of its estimation and validation. This paper discusses statistical methods enabling PD estimations with consideration of the retail character of a credit portfolio. The author refers to the issue of defining default and to the way of calculating the number of days in arrears. This paper presents the results of research studies obtained on the basis of retail credit portfolio. For selected sub-portfolios, the author makes a comparison of the probability of default, which enables the explicit risk assessment.
Mathematical Economics, 2011, Nr 7 (14), s. 199-212
Keywords: credit risk; probability of default; credit scoring